A Cognitive-Axiological Analysis of Gymshark’s Adverts - García Carreño, Ariadna (2021)
Gymshark is a British fitness clothing company that, in less than 10 years, has become a multi-million dollar company. This company’s success is linked to its promotion through an advertising discourse which emphasizes an ethical system that significantly differentiates it from other active-wear companies on the market. To do this, Gymshark relies on a digital advertising discourse, presented through social networks such as Instagram or YouTube to reach a young audience more immediately. Thus, this paper aims to analyze the persuasive techniques used in eight Gymshark ads to promote clothing collections and fitness challenges, especially the use of cognitive and axiological tools: conceptual metaphors and metonymies, image schemas and colour. Consequently, this analysis relies on Cognitive Linguistics theory (Lakoff & Johnson, 1980; Ruiz de Mendoza, 2002; Evans & Green, 2006), its application to advertising discourse (Forceville, 1996; 2008; 2009), the axiological notions proposed by Krzeszowski (1990) and some considerations on the use of colour. The results show that Gymshark’s advertising discourse prioritizes the use of cognitive tools to associate the products and the brand with positive axiological values beyond those strictly linked to fitness; therefore, this constitutes a key factor in the development of the consumer’s attraction to the brand.